Divine, demonic, and disordered : women without men in Song Dynasty China - Cheng, Hsiao-wen. (Seattle : University of Washington Press, 2021)
"A variety of Chinese writings-medical texts, religious treatises, fiction, and anecdotes-from the Song period (960-1279) depict women who were considered peculiar because their sexual bodies did not belong to men. These were women who refused to marry, were considered unmarriageable, or were married but denied their husbands sexual access, thereby removing themselves from social constructs of female sexuality defined in relation to men. As elite male authors attempted to make sense of these incomprehensible women whose sexual bodies were unavailable to them, they were forced to contemplate the purpose of women's bodies and lives apart from wifehood and motherhood. This raised troubling new questions about normalcy, desire, sexuality, and identity. In Divine, Demonic, and Disordered Hsiao-wen Cheng considers accounts of "manless women," many of which depict women who suffered from "enchantment disorder" or who engaged in "intercourse with ghosts"-conditions with specific symptoms and behavioral patterns. Through her questioning of conventional binary gender analyses and heteronormative assumptions, she shifts attention away from women's reproductive bodies and familial roles and offers historians of China and readers interested in women, gender, sexuality, medicine, and religion a fresh look at the unstable meanings attached to women's behaviors and lives even in a time of codified patriarchy"--
Part I. Reconfiguring gender, sexuality, and illness -- 1. "Husbandless women" in medicine -- 2. Ghost intercourse in medical and daoist contexts -- Part II. Inconvenient female sexuality and multivocal narratives -- 3. Enchantment disorder and pre-song tales -- 4. Enchanted women in song anecdotes -- Part III. Gendered identities and female celibacy -- 5. Gendered practice and renunciant identity -- 6. Meanings of female celibacy -- Conclusion.
Includes bibliographical references and index.
Keywords: Women -- Sexual behavior -- China; Celibacy -- China; China -- History Song dynasty, 960-1279 -- Anecdotes